Dry Matter Intake and Body Condition Score in Ascending Descending Phase of Lactation in Gir Cows Supplemented with Bypass Fat and Choline - Gamit, Viral V; Gadariya, Mahesh R; Patbandha, Tapas K; Odedra, Mulraj D; Savsani, Harish H; Gamit, Krishna C (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
Present study was conducted to observe dry matter intake on % body weight (DMI%BW) and body condition score (BCS) pattern in ascending-descending phase of lactation in Gir cows. A total of 18 cows were randomly assigned to three groups, with each group consisting of six cows. Cows in control group were fed basal ration, while in treatment 1 (T-1) were supplemented with bypass fat (10 g/kg of milk) with basal ration and in treatment 2 (T-2) were supplemented with bypass fat (10 g/kg of milk) and choline (45 g/day/ cow) with basal ration from 2nd to 25th week of lactation. Lactation period was divided into ascending phase from 2nd to 9th week and descending phase from 10th to 25th week after parturition based on milk production pattern. Supplementation regime did not affect BCS during ascending phase and first three fortnights of descending phase, but from 17th week of lactation the BCS was significantly higher in both supplemented groups than control. The DMI%BW did not vary among the groups. There was a highly significant strong negative correlation between DMI%BW and BCS in all groups during ascending phase. However, during descending phase, degree of association was weak in control, strong in T-1 and moderate in T-2 groups. The results showed that additional energy intake from bypass fat and choline supplementation contributed significant gain in BCS from 17th week of lactation (or from 4th fortnight of descending phase of lactation).